BSACI guideline for the diagnosis and management of peanut and tree nut allergy. Issue 6 (June 2017) - Stiefel, G.; Anagnostou, K.; Boyle, R. J.; Brathwaite, N.; Ewan, P.; Fox, A. T.; Huber, P.; Luyt, D.; Till, S. J.; Venter, C.; Clark, A. T.
Summary: Peanut nut and tree nut allergy are characterised by IgE mediated reactions to nut proteins. Nut allergy is a global disease. Limited epidemiological data suggest varying prevalence in different geographical areas. Primary nut allergy affects over 2% of children and 0.5% of adults in the UK. Infants with severe eczema and/or egg allergy have a higher risk of peanut allergy. Primary nut allergy presents most commonly in the first five years of life, often after the first known ingestion with typical rapid onset IgE‐mediated symptoms. The clinical diagnosis of primary nut allergy can be made by the combination of a typical clinical presentation and evidence of nut specifc IgE shown by a positive skin prick test (SPT) or specific IgE (sIgE) test. Pollen food syndrome is a distinct disorder, usually mild, with oral/pharyngeal symptoms, in the context of hay fever or pollen sensitisation, which can be triggered by nuts. It can usually be distinguish clinically from primary nut allergy. The magnitude of a SPT or sIgE relates to the probability of clinical allergy, but does not relate to clinical severity. SPT of ≥ 8 mm or sIgE ≥ 15 KU/L to peanut is highly predictive of clinical allergy. Cut off values are not available for tree nuts. Test results must be interpreted in the context of the clinical history. Diagnostic food challenges are usually not necessary but may be used to confirm or refute a conflicting history and test result. As nut allergy is likely to be a long‐lived disease, nut avoidance advice is the cornerstone of management. Patients should be provided with a comprehensive management plan including avoidance advice, patient specific emergency medication and an emergency treatment plan and training in administration of emergency medication. Regular re‐training is required.